Aromatase inhibition remodels the clonal architecture of estrogen-receptor-positive breast cancers - Christopher A. Miller (Nature Portfolio, 2016)
Aromatase inhibitors are used to treat oestrogen-receptor-positive breast cancer. Here, the authors use genomic approaches to analyse tumours before and after neo-adjuvant treatment and find that treatment alters the clonal landscape of the tumours.